2008
DOI: 10.1080/03004430701536582
|View full text |Cite
|
Sign up to set email alerts
|

Does improving joint attention in low‐quality child‐care enhance language development?

Abstract: This study examined effects of professional development for child-care staff on language acquisition of children ages 14-36 months. Child-care staff from 44 child-care centres agreed to participate in the study. Child-care staff from one-half of the child-care centres were randomly assigned to a onetime, four-hour workshop followed by three classroom visits over the subsequent three months. This treatment was designed to increase frequency and quality of joint attention episodes between the child-care staff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Our findings agree with the significant qualitative and quantitative research base, which demonstrates the benefits of educating parents on proper reading techniques and provides useful models for practitioners charged with improving childhood literacy and school readiness (Huebner, 2000;Phillips et al, 2008;Rudd et al, 2008;Sénéchal, 2006). They also offer clear evidence that appropriately designed interventions can promote an increase in the amount of time parents spend reading with their preschoolers.…”
Section: Discussion and Review Implicationssupporting
confidence: 90%
“…Our findings agree with the significant qualitative and quantitative research base, which demonstrates the benefits of educating parents on proper reading techniques and provides useful models for practitioners charged with improving childhood literacy and school readiness (Huebner, 2000;Phillips et al, 2008;Rudd et al, 2008;Sénéchal, 2006). They also offer clear evidence that appropriately designed interventions can promote an increase in the amount of time parents spend reading with their preschoolers.…”
Section: Discussion and Review Implicationssupporting
confidence: 90%
“…In a recent study by Rudd et al (2008), it was found that caregivers of infants and toddlers could be trained through a 4-h professional development experience to engage in more frequent and better types of interactions with toddlers. However, the study found considerable variability in the caregivers' levels of implementation of the process.…”
Section: Coachingmentioning
confidence: 97%
“…Certainly, the ability to efficiently attend to both social cues and content being presented is a skill that successful learners exhibit [15,33]. Examining the potential role joint attention plays in the complex process of preschool learning is a logical extension of research with young children showing that individual differences in joint attention relate to both future language ability and social behavior [10,38,48,[54][55][56].…”
Section: Implications and Future Directionsmentioning
confidence: 99%